Incentives for Combining Structure and Process Quality to Improve Outcome in Rheumatic Treatment. (September 2022) - Romeyke, Tobias; Noehammer, Elisabeth; Stummer, Harald
The study investigates the effects of multidisciplinary treatment for rheumatic treatment regarding (a) financial feasibility based on costs/remuneration in comparison to conventional treatment and (b) Patient reported outcome measures (Proms) to check for effectiveness. For (a), cost data and remuneration with and without multimodal rheumatologic complex treatment (MRCT) is analysed, including cost types. The database encompasses 18, 794 treatment cases. For (b), a case study with retrospective patient data analysis ( N = 375, all treated in a specialized German hospital) regarding self-reported quality of life and physical functions is carried out for subjects receiving MRCT. While conventional treatment is fully covered, MRCT is only incentivized for cases with long in-patient treatment, so financial feasibility for hospitals is limited. Patients with MRCT reported significant improvements in quality of life ( p < .001; Nottingham Health Profile) as well as in physical functions (Functional Questionnaire Hannover [FFbH], p < .001) at discharge compared to admission. As short-term MRCT is not fully remunerated, less severe cases may not receive adequate care. Financial incentives should at least cover the costs incentivize the offer and thus ensure patient access to MRCT. Measuring the outcomes of the treatment process by means of Proms can contribute to the internal quality management. It also offers an inter-institutional benchmark to service providers, which can be used as a basis for performing comparative quality measurements and researching effectiveness.